The Efficacy of Adalimumab Treatment in Pediatric Non-Infectious Uveitis: A Retrospective Cohort Study - Kübra Özdemir Yalçınsoy; Osman Özen; Yasemin Özdamar Erol; Pınar Çakar Özdal (Türk Oftalmoloji Dergisi)
Objectives: To evaluate the clinical features of pediatric non-infectious uveitis (NIU) patients treated with adalimumab (ADA) and the efficacy of ADA in patients unresponsive to conventional immunosuppressive therapy. Materials and Methods: The records of 91 NIU patients aged ≤16 years who received ADA therapy were evaluated retrospectively. The patients’ demographic and clinical characteristics and treatment approaches were recorded. The efficacy of ADA in patients treated for at least 1 year after failure of conventional immunosuppressive treatment was evaluated by comparing the best corrected visual acuity (BCVA), severity of intraocular inflammation, uveitis flare-ups, topical and systemic corticosteroid (CS) use, and central macular thickness (CMT) values before and after ADA treatment. Results: The study included 103 eyes of 53 patients, of whom 29 (54.7%) were female. The mean age at presentation was 8.2±3.4 (range: 3-16) years. The mean follow-up period was 41.6±28.2 (range: 18-120) months. Twenty-six patients (49.0%) had anterior uveitis, 22 (41.5%) had intermediate uveitis, and 5 (9.4%) had panuveitis. The mean duration of ADA treatment was 23.0±13.7 (range: 12-60) months. Uveitis flare-ups developed in only 13 patients (24.5%) while on ADA treatment. When pre- and post-treatment periods were compared, the mean number of uveitis flare-ups, intraocular inflammation severity, mean dose of topical and systemic CS, and mean CMT values were significantly lower in the post-treatment period (p<0.05). The mean BCVA was significantly improved after 6 and 12 months of ADA treatment compared to the pre-treatment visual acuity (p<0.05). Conclusion: ADA effectively controlled intraocular inflammation, reducing the need for systemic and topical CS and improving visual outcomes in pediatric NIU.